2020
DOI: 10.1108/cdi-11-2018-0297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of career shocks on Indian MBA careers: an exploratory study

Abstract: PurposeThe study explores career shocks in the Indian context and examines their impact on the career development of people with MBAs.Design/methodology/approachIn-depth, semi-structured interviews with 41 Indian MBA graduates were thematically analysed to identify career shocks that resulted in different types of transitions. Eight themes were identified based on ongoing and iterative comparison of these instances.FindingsOutcomes relating to competitive examinations that determined entry into various occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…The fourth article features a qualitative study among 41 Indian MBA graduates. Nair and Chatterjee (2021) specifically looked at how career shocks may trigger career transitions. Their findings indicate that career shocks may lead to different career transition types and trajectories.…”
Section: Lessons Learned From the Special Issuementioning
confidence: 99%
“…The fourth article features a qualitative study among 41 Indian MBA graduates. Nair and Chatterjee (2021) specifically looked at how career shocks may trigger career transitions. Their findings indicate that career shocks may lead to different career transition types and trajectories.…”
Section: Lessons Learned From the Special Issuementioning
confidence: 99%
“…Researchers have also found evidence that negative organizational-related career shocks can impair career optimism (Hofer et al, 2020) and that career shocks moderate the indirect relationship between career competencies and perceived employability (Blokker et al, 2019). Together, these results indicate that careers do not unfold in a vacuum (Felix et al, 2018) and that unexpected events play an important role in one's career development (Nair and Chatterjee, 2020;Felix and Cavazotte, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…, 1995; Gati and Perez, 2014). The literature revealed that career shocks can have effects that may vary based on gender (Nair and Chatterjee, 2020; Akkermans et al. , 2021).…”
Section: Theoretical Foundation Literature Review and Research Questionsmentioning
confidence: 99%
“…, 2021). For example, in India, women reported arranged marriage as a career shock that negatively impacts their career paths (Nair and Chatterjee, 2020).…”
Section: Theoretical Foundation Literature Review and Research Questionsmentioning
confidence: 99%